2000
DOI: 10.1159/000016092
|View full text |Cite
|
Sign up to set email alerts
|

Early <sup>99m</sup>Tc-Ethylcysteinate Dimer Brain SPECT Patterns in the Acute Phase of Stroke as Predictors of Neurological Recovery

Abstract: Objectives: Accurate prediction of outcome in acute stroke would help in identifying subgroups of patients for therapeutic trials and intravenous thrombolysis. The purpose of this study was to prospectively test the hypothesis that brain SPECT, with 99mTc-L,L-ethylcysteinate dimer (ECD), a tracer sensitive to cell function, performed in the first hours after stroke onset, adds predictive power to concomitant neurological evaluation. Methods: Twenty-four patients with a first-ever middle cerebral art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…As was expected, a deeper or larger ischemic lesion predicted a poorer functional outcome. In the past 2 decades, many studies using perfusion SPECT [2,[29][30][31][32][33][34][35] successfully demonstrated the ischemic threshold in acute stroke (Table 1). These studies commonly demonstrated that most of the ischemic lesions under a certain rCBF level or most of the hyperemic lesions would progress to complete infarction.…”
Section: Identifying Risky Patients For Early Reperfusion Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…As was expected, a deeper or larger ischemic lesion predicted a poorer functional outcome. In the past 2 decades, many studies using perfusion SPECT [2,[29][30][31][32][33][34][35] successfully demonstrated the ischemic threshold in acute stroke (Table 1). These studies commonly demonstrated that most of the ischemic lesions under a certain rCBF level or most of the hyperemic lesions would progress to complete infarction.…”
Section: Identifying Risky Patients For Early Reperfusion Therapymentioning
confidence: 99%
“…These imaging modalities allow us to understand the pathophysiology in ischemic stroke and help determine the diagnosis, treatment, and management. Measurement of rCBF and metabolism plays critical roles in acute ischemic stroke because they directly correlate with the prognosis of functional recovery [1][2][3][4]. In the past 3 decades, many studies using SPECT or PET evaluated the cerebral hemodynamic or metabolic changes in acute ischemic stroke, and the usefulness of rCBF and metabolism measurement was established.…”
Section: Introductionmentioning
confidence: 99%
“…All patients with transient ischemia had count rate densities more than 70% of the respective contralateral ROI, whereas all patients with subsequent infarction had values less than 70%. Mahagne et al [15] indicated that the degree of ECD cortical uptake reduction, measured on early brain SPECT, is a strong predictor of spontaneous neurological recovery and functional outcome They found a strong correlation between the extent of irreversibly damaged cortex defined as ECD uptake below 40% of maximal uptake. The apparently better predictive value of ECD over HMPAO may reflect this tracer's brain retention mechanisms which are weighted more towards cell function than towards perfusion.…”
Section: Spectmentioning
confidence: 99%
“…Applying the above concepts to other imaging techniques, we showed that although perfusion SPECT yielded globally similar findings as PET with respect to patient categorization and prognostication, this was at the cost of reduced accuracy due to lack of both quantification of CBF and metabolic information [45,46,47]. This, added to the time needed to complete a SPECT study, made this approach not very promising.…”
Section: Mapping the Penumbramentioning
confidence: 99%